Avaliação linear do côndilo mandibular em indivíduos padrão II submetidos à cirurgia ortognática - Perez, Roble Casares (2017)
Surgical orthodontic treatment plays a prominent role in rehabilitating skeletal deformities of the oral and maxillofacial region. However, there is still a limit to its use. This encourages researchers to seek knowledge and techniques which ensure the highest standard of excellence in diagnosis, treatment planning, and prognosis. Orthognathic surgeries may interfere with the compression of the temporomandibular joint associated structures causing irreversible internal lesions. There are very few studies in academic literature evaluating the changes in the bone surface of the mandibular condyle in standard II patients with mandibular deficiency who have been submitted to surgical orthodontic treatment using cone bean computed tomography allied to next generation software technology. The aim of this study was to evaluate linearly the changes in the bone surface of the mandibular condyle in standard II patients who have skeletal change and have been submitted to surgical orthodontic treatment under the software INVESALIUS 3.0® (CTI - Centro de Tecnologia da Informação Renato Archer, Campinas, Brazil). Samples of medical records of 17 patients (3 males and 14 females) aged 18 to 60 who have already been submitted to surgical procedures with defined protocol by the same team are available